2013
DOI: 10.1111/bjh.12318
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic risk in patients with immune thrombocytopenia and its association with antiphospholipid antibodies

Abstract: SummaryPatients with immune thrombocytopenia (ITP) paradoxically have an increased risk of thrombosis. The presence of antiphospholipid antibodies (aPL) has been observed in a substantial proportion of ITP patients, but its clinical significance remains to be established. This study retrospectively investigated the prevalence and clinical significance of aPL in ITP patients and assessed the risk factors for thrombosis. One hundred and sixty-five subjects with ITP were included in the study and followed for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 32 publications
(69 reference statements)
2
38
2
Order By: Relevance
“…‘Annualised’ cumulative incidence and risk . Following ITP diagnosis, the pooled ‘annualised’ cumulative risk for TE was 2.97%/yr (Fig. ) and the pooled ‘annualised’ cumulative incidence for TE was 1.29%/yr (Figure S2, Supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…‘Annualised’ cumulative incidence and risk . Following ITP diagnosis, the pooled ‘annualised’ cumulative risk for TE was 2.97%/yr (Fig. ) and the pooled ‘annualised’ cumulative incidence for TE was 1.29%/yr (Figure S2, Supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…41 One potential explanation for this difference may be that in HIT, monocytes, neutrophils, and endothelial cells are targeted for activation as well. 11,36,42,43 However, the involvement and mechanism by which these cells contribute to thrombosis has received far less attention than platelets.…”
Section: Discussionmentioning
confidence: 99%
“…102 APLA occurs in up to 40% of patients with ITP. 103 While these antibodies do not alter the course of ITP, several studies suggest that the presence of APLA, particularly the lupus anticoagulant, increase the risk of thrombosis, 103,104 with 5-year thrombosis free-survival of 39.9% and 97.7%, respectively, in patients with ITP and LA, versus ITP alone. A small study reported no significant increase in thrombotic events after splenectomy in patients with ITP and APLA, though there was a trend towards more arterial events.…”
Section: Systemic Lupus Erythematosus (Sle) and Antiphospholipid Antimentioning
confidence: 99%